When solving for y in this problem(4x+y=2) we need to get y by itself in the equation.
To do this we need to move 4x over to the right side of the equation. To do this we subtract, 4x from both sides of the equation.
Key Point to remember: What we do to one side of the equation we have to do the same to the other side of the equation.
So, here are the steps to move 4x over to the other side of the equation so y can be by itself since we are solving for y.
We subtract 4x from each side of the original equation. This leaves y by itself.
4x+y - 4x = 2 -4x
+y = 2 - 4x or y = 2 - 4x (We have just solved for y. This is our final answer)
=> `y = -4x+2`